The complete chloroplast genome of Rubus pinfaensis, an edible and medicinal dual-purpose plant - Yiyun Tang; Chunhua Li; Liping Lei; Jingxiu Xiao; Ying-an Zhu (Mitochondrial DNA. Part B. Resources, 2023)
Rubus pinfaensis H. Lév. & Vaniot is of great importance in the phylogeny and evolution amongst Rosaceae, genus Rubus L. plants. The chloroplast genome of R. pinfaensis was reported in this study, which is 155,523 bp in size, with an average GC content of 37.13%. The complete chloroplast genome has a typical quadripartite structure, including a large single copy (LSC) region (85,211 bp) and a small single copy (SSC) region (18,718 bp), which were separated a pair of inverted repeats (IRs, 25,797 bp). This plastome contained 129 different genes (112 unique), including 85 protein-coding genes (79 unique), 36 tRNA genes (29 unique), and 8 rRNA genes (4 unique). The chloroplast genome of R. pinfaensis has completed that will be based on the phylogeny and genomic studies in the family Rosaceae, genus Rubus L.